Basic studies of protein folding and stability: the folding of related protein families - Clarke, Jane (Henry Stewart Talks, 2007)
The basics of protein folding studies: protein stability (thermodynamics) and protein folding kinetics, The shape and interpretation of simple chevron plots, How protein engineering phi value analysis can be used to investigate the structure of the transition state for protein folding, How studies of the folding of related proteins can simplify the problem of investigating how proteins fold, Comparison of the folding of complex, all-beta immunoglobulin-like proteins to the folding of simple 3-helix bundles
Archived at 2016/04/17